“The Impact of the Exogenous Shock on Transaction Costs in B2C Relationship: A Survey Study in Poland” - Jarosław PLICHTA; Adam SAGAN; Grazyna PLICHTA (Communications of International Proceedings, 2025)
This study investigates how exogenous shocks, specifically pandemic, affect transaction costs in B2C relationships within the Polish market. The motivation stems from a growing need to understand consumer behavior shifts under crisis conditions and how institutions mediate these responses. Utilizing the lens of institutional economics and transaction cost theory, the research examines how key behavioral factors—trust, opportunism, and information asymmetry—influence consumer decisions during disruptions. A quantitative research design was employed, using a structural equation modeling (SEM) approach. Data were gathered through a CAWI survey of 578 Polish consumers in March 2021, focusing on their e-commerce behavior during the pandemic. The model incorporated six latent variables, including exogenous shock (PAN), trust (HON), opportunism (INT), information asymmetry (INF), transaction costs (COST), and online purchasing behavior (BUY). The findings demonstrate that opportunism and trust significantly mediate the relationship between exogenous shocks and online purchasing behavior. In contrast, information asymmetry showed no significant direct effect. Transaction costs emerged as a key outcome variable influenced by both opportunism and trust, subsequently affecting purchase behavior. The pandemic enhanced digital engagement by lowering perceived transaction costs and accelerating consumers’ transition to online platforms. The study highlights the resilience of B2C market relationships during crises and emphasizes the importance of trust-building mechanisms and transparency in reducing transaction costs. These insights offer practical guidance for businesses and policymakers aiming to foster consumer confidence and strengthen institutional stability in times of disruption.
Keywords: Exogenous Shocks; Transaction Costs; Consumer Trust; E-commerce Behavior